Easier said than done: a qualitative study conducted in the USA exploring Latino family child care home providers as role models for healthy eating and physical activity behaviours. Issue 11 (12th November 2017) - Lindsay, Ana Cristina; Greaney, Mary L; Wallington, Sherrie F; Wright, Julie A
Abstract : Objective: Latinos are the largest and most rapidly growing minority population group in the USA and are disproportionally affected by obesity and related chronic diseases. Child care providers likely influence the eating and physical activity behaviours of children in their care, and therefore are important targets for interventions designed to prevent childhood obesity. Nonetheless, there is a paucity of research examining the behaviours of family child care home (FCCH) providers and whether they model healthy eating and physical activity behaviours. Therefore, this study explored Latino FCCH providers' beliefs and practices related to healthy eating, physical activity and sedentary behaviours, and how they view their ability to serve as role models for these behaviours for young children in their care. Methods: This is a qualitative study consisting of six focus groups conducted in Spanish with a sample of 44 state-licensed Latino FCCH providers in the state of Massachusetts. Translated transcripts were analysed using thematic analyses to identify meaningful patterns. Results: Analyses revealed that Latino FCCH providers have positive beliefs and attitudes about the importance of healthy eating and physical activity for children in their care, but personally struggle with these same behaviours and with maintaining a healthy weight status. The ability of Latino FCCH providers to model healthy eating and physical activity may be limited by their low self-efficacy in their ability to be physically active, eat a healthy diet and maintain a healthy weight. Conclusions: Interventions designed to improve healthy eating and physical activity behaviours of children enrolled in FCCHs should address providers' own health behaviours as well as their modelling of these health behaviours. Future research can build on the findings of this qualitative study by quantifying Latino FCCH providers' eating and physical activity behaviours, and determining how these behaviours influence behaviours and health outcomes of children in their care.